The Effect Of Special Exercises On Learning Hurdle Clearing And The Rhythmic Triple Step Of 100m Hurdles Aged 14 – 15 Years Old - Hassan, Mohammed; Haitham, Ahmed (Journal of Physical Education, 2018)
The Effect Of Special Exercises On Learning Hurdle Clearing And The Rhythmic Triple Step Of 100m Hurdles Aged 14 – 15 Years Old The importance of the research lies in identifying the effect of special exercises using teaching aids for learning the basic phases of hurdles; clearance and rhythmic triple steps. The problem of the research lies in the lack of interest in training these two phases. The researchers came up with some conclusions and recommendations. Keywords: special exercises, hurdles, clearing.